Recent progress on nuclear receptor RORγ modulators. Issue 18 (15th September 2016) - Cyr, Patrick; Bronner, Sarah M.; Crawford, James J.
Graphical abstract: Abstract: The retinoic acid receptor-related orphan receptor RORγ plays key roles in the development and differentiation of TH 17 cells, and thus in IL-17 expression, thymocyte development and regulation of metabolism. With the recent progression into phase 2 clinical trials of both oral and topically administered inverse agonists, and with others close behind, there is significant interest in the discovery of RORγ modulators. This digest covers key developments around RORγ agonists, antagonists and inverse agonists; orthosteric and allosteric binders; and aims to summarize the available information concerning the potential utility of RORγ modulators.